Cost of Capital and Bursa Malaysia Listed Company - Lim, Ru Po (2005)
This study estimates the cost of capital of 226 securities listed in the Bursa Malaysia. The study's sample covers the period from January 1992 to August 2005. The cost of capital using Ordinary Least Squares Regression is first obtained. Next, the cost of capital using the 3 techniques which are the Scholes-Williams, the Dimson and Fowler-Rorke beta estimators for correction for nonsynchronous bias due to thin trading is applied. This study differs from the previous studies as this extends by using the market risk premium to calculate the beta while the previous studies used the market return to estimate the betas. The results show that the cost of capital using the Fowler-Rorke 1 lag/lead specification of the Market is best for the Malaysian security market. In this study, we found that the hotel sector has the higest average cost of capital with a value of 8.13 percent. In addition, we also found that 210 companies have recorded negative average annual returns minus cost of capital. The stability tests using the Cross-Sectional Correlation Coefficient and the t-test show that at 0.05 level of significance, there is stability for betas across the two subperiods.